2010
DOI: 10.2527/jas.2009-2236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary crude protein source on hormone and follicle characteristics in beef heifers1

Abstract: Ground, raw soybeans (SB), or dried distillers grain plus solubles (DDGS) were utilized in heifer development diets to determine the effect of dietary fat and protein source on hormone and follicle characteristics and ADG. The experiment was conducted over 2 yr with 100 June-born heifers (199 +/- 2 kg initial BW, n = 50 per yr). The experimental periods were 157 and 207 d in yr 1 and 2, respectively. Heifers were provided a dietary supplement (DM basis) of 1.23 kg of SB and 0.40 kg of corn or 1.65 kg of DDGS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Scholljegerdes et al (2009) recorded lower tissue concentrations of LH and IGF-1, follicle numbers, systemic oestradiol and overall conception rate in beef cows supplemented with high-linoleate safflower seeds compared with unsupplemented controls. SimiIarly, Martin et al (2010) observed no advantage of supplementing heifers with soya beans in either productive or reproductive efficiency. In a series of experiments conducted with beef heifers, Childs et al (2008aChilds et al ( , 2008bChilds et al ( and 2008c failed to establish any positive effects of enriching diets with rumen bypass n-3 fatty acids on a range of reproductive variables including steroid concentrations, follicle size and on the quantity or quality of embryos, following superovulation.…”
Section: Nutritional Effects On Conception and Pregnancy Ratementioning
confidence: 98%
“…Scholljegerdes et al (2009) recorded lower tissue concentrations of LH and IGF-1, follicle numbers, systemic oestradiol and overall conception rate in beef cows supplemented with high-linoleate safflower seeds compared with unsupplemented controls. SimiIarly, Martin et al (2010) observed no advantage of supplementing heifers with soya beans in either productive or reproductive efficiency. In a series of experiments conducted with beef heifers, Childs et al (2008aChilds et al ( , 2008bChilds et al ( and 2008c failed to establish any positive effects of enriching diets with rumen bypass n-3 fatty acids on a range of reproductive variables including steroid concentrations, follicle size and on the quantity or quality of embryos, following superovulation.…”
Section: Nutritional Effects On Conception and Pregnancy Ratementioning
confidence: 98%